Evaluation of diesel fleet emissions and control policies from plume chasing measurements of on-road vehicles. (December 2015) - Lau, Chui Fong; Rakowska, Agata; Townsend, Thomas; Brimblecombe, Peter; Chan, Tat Leung; Yam, Yat Shing; Močnik, Griša; Ning, Zhi
Abstract: Vehicle emissions are an important source of urban air pollution. Diesel fuelled vehicles, although constituting a relatively small fraction of fleet population in many cities, are significant contributors to the emission inventory due to their often long mileage for goods and public transport. Recent classification of diesel exhaust as carcinogenic by the World Health Organization also raises attention to more stringent control of diesel emissions to protect public health. Although various mandatory and voluntary based emission control measures have been implemented in Hong Kong, there have been few investigations to evaluate if the fleet emission characteristics have met desired emission reduction objectives and if adoption of an Inspection/Maintenance (I/M) programme has been effective in achieving these objectives. The limitations are partially due to the lack of cost-effective approaches for the large scale characterisation of fleet based emissions to assess the effectiveness of control measures and policy. This study has used a plume chasing method to collect a large amount of on-road vehicle emission data of Hong Kong highways and a detailed analysis was carried out to provide a quantitative evaluation of the emission characteristics in terms of the role of high and super-emitters in total emission reduction, impact of after-treatment on the multi-pollutants reduction strategy and the trend of NO2 emissions with newer emission standards. The study revealed that not all the high-emitters are from those vehicles of older Euro emission standards. Meanwhile, there is clear evidence that high-emitters for one pollutant may not be a high-emitter for another pollutant. Multi-pollutant control strategy needs to be considered in the enactment of the emission control policy which requires more comprehensive retrofitting technological solutions and matching I/M programme to ensure the proper maintenance of fleets. The plume chasing approach used in this study also shows to be a useful approach for assessing city wide vehicle emission characteristics. Highlights: Gini coefficient was used to quantify the inequality of emission within fleets. Multi-pollutant control strategy needs to control vehicle emissions. There exist high emitters even in newer vehicle fleets. Identification and removal of high emitters is a cost-effective emission control.